Surgical Regenerative Treatments for Peri-Implantitis: Meta-analysis of Recent Findings in a Systematic Literature Review - Povilas Daugela; Marco Cicciù; Nikola Saulacic (Stilus Optimus, 2016)
Objectives: The purpose of the present study was to systematically review the literature on the surgical regenerative treatment of the peri-implantitis and to determine an effective therapeutic predictable option for their clinical management. Material and Methods: The study searched MEDLINE and EMBASE databases from 2006 to 2016. Clinical human studies that had reported changes in probing depth (PD) and/or bleeding on probing (BOP) and/or radiologic marginal bone level (RBL) changes after peri-implantitis surgical treatment at 12-month follow-up or longer were included accordingly to PRISMA guidelines. Results: The initial search obtained 883 citations. After screening and determination of eligibility, 18 articles were included in the review. The meta-analysis of selected studies revealed that the weighted mean RBL fill was 1.97 mm (95% confidence interval [CI] = 1.58 to 2.35 mm), PD reduction was 2.78 mm (95% CI = 2.31 to 3.25 mm), and BOP reduced by 52.5% (95% CI = 41.6 to 63.1%). Defect fill in studies using and not using barrier membranes for graft coverage was 1.86 mm (95% CI = 1.36 to 2.36 mm) and 2.12 mm (95% CI = 1.46 to 2.78 mm) correspondingly. High heterogeneity among the studies regarding defects morphology, surgical protocols, and selection of biomaterials were found. Conclusions: All included studies underlined an improvement of clinical conditions after the surgical regenerative treatment of peri-implantitis, however, there is a lack of scientific evidence in the literature regarding the superiority of the regenerative versus non-regenerative surgical treatment. The presence of a barrier membrane or submergence in the regenerative procedure does not seem to be fundamental in order to obtain clinical success of the surgery.